2021
DOI: 10.1038/s41538-021-00087-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-based environmental monitoring of a dairy processing facility highlights the challenges associated with low microbial-load samples

Abstract: Efficient and accurate identification of microorganisms throughout the food chain can potentially allow the identification of sources of contamination and the timely implementation of control measures. High throughput DNA sequencing represents a potential means through which microbial monitoring can be enhanced. While Illumina sequencing platforms are most typically used, newer portable platforms, such as the Oxford Nanopore Technologies (ONT) MinION, offer the potential for rapid analysis of food chain microb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…On the other hand, the presence of microorganisms in the samples could be due to contaminations that occurred after heat treatments and that originated from the surrounding production environment [ 8 ]. Various studies have found that the microbial species that colonize production facilities and the air in the manufacturing areas have a significant impact on the microbial compositions of dairy products [ 31 , 32 , 33 ]. A study showed that the same yeast species were detected in cheese and in the environment of its production facility, although at varying abundances [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of microorganisms in the samples could be due to contaminations that occurred after heat treatments and that originated from the surrounding production environment [ 8 ]. Various studies have found that the microbial species that colonize production facilities and the air in the manufacturing areas have a significant impact on the microbial compositions of dairy products [ 31 , 32 , 33 ]. A study showed that the same yeast species were detected in cheese and in the environment of its production facility, although at varying abundances [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors could account for the numerical difference in species level classification of the Staphylococcus strain, where Illumina sequencing afforded greater taxonomic resolution than ONT sequencing, as S. hominis is specifically classified within the S. haemolyticus group ( Becker et al, 2014 ). Additionally, for shotgun sequencing with ONT, MDA amplification was needed to generate sufficient quantities of DNA required for sequencing, which has been previously found to introduce some biases ( McHugh et al, 2021 ). Despite all these points, as improvements are made to the sequencing technology and analytical tools, coupled with its advantages in portability, time effectiveness and the possibility of real-time analysis, there is great potential for the use of ONT sequencing in characterising microbial communities in food and food-related environments.…”
Section: Discussionmentioning
confidence: 99%
“…Biosensors are utilized to increase quality of life in a variety of applications. The quality, safety, and upkeep of food items as well as their processing are difficult in food processing industries, and hence the food sector would benefit from cost-effective technologies for food authentication and monitoring [ 121 , 122 , 123 ]. Potentiometric alternating biosensing devices are also used to detect the changes in pH caused by ammonia, and have been used to identify E. coli [ 124 ]; ingredients were mixed in a sonicator to separate the bacteria from the food [ 125 ].…”
Section: Applicationsmentioning
confidence: 99%